Implementation of Sharia Bank Integrated Marketing Communication in Increasing the Number of Customers - Karmila Karia (Journal Of Institution And Sharia Finance, 2021)
This study aims: to describe the implementation of Integrated Marketing Communications that can increase the number of customers at Bank Syariah Indonesia (BSI) Kcp Andi Djemma Palopo City. The type of research used by researchers is qualitative research with descriptive research types. The location of the research was carried out at Bank Syariah Indonesia KCP Andi Djemma, Palopo City. The subjects in this study were Marketing at Bank Syariah Indonesia (BSI) KCP Andi Djemma, Palopo City. With the research instruments used, namely in the form of interview guidelines and observation guidelines. Data collection techniques used are observation techniques, interviews and documentation. The data analysis technique used is by means of data reduction, data presentation and drawing conclusions. The results of this study illustrate that: In the marketing process of Bank Syariah Indonesia (BSI) Kcp Andi Djemma, Palopo City, which applies an integrated marketing communication model, it can be said that it is able to increase the number of its customers, this is based on efforts to carry out marketing and other things, namely in terms of awareness self and society's perspective on religion by paying attention to sharia matters in life. This certainly has a positive effect on the development of Islamic banking in Indonesia, which in fact is one of the countries with the largest Muslim community in the world.